Changing inputs of continental and submarine weathering sources of Sr to the oceans during OAE 2. (15th June 2021) - Nana Yobo, Lucien; Brandon, Alan D.; Holmden, Chris; Lau, Kimberly V.; Eldrett, James
Abstract: Ocean anoxic events (OAE) are characterized by increased organic content of marine sediment on a global scale with accompanying positive excursions in sedimentary organic and inorganic δ 13 C values. To sustain the increased C exports and burial required to explain the C isotope excursion, increased supplies of nutrients to the oceans are often invoked during ocean anoxic events. The potential source of nutrients in these events is investigated in this study for Oceanic Anoxic Event 2, which spans the Cenomanian-Turonian boundary. Massive eruptions of one or more Large Igneous Provinces (LIPs) are the proposed trigger for OAE 2. The global warming associated with volcanogenic loading of carbon dioxide to the atmosphere has been associated with increased continental weathering rates during OAE 2, and by extension, enhanced nutrient supplies to the oceans. Seawater interactions with hot basalts at LIP eruption sites can further deliver ferrous iron and other reduced metals to seawater that can stimulate increased productivity in surface waters and increased oxygen demand in deep waters. The relative importance of continental and submarine weathering drivers of expanding ocean anoxia during OAE 2 are difficult to disentangle. In this paper, a box model of the marine Sr cycle is used to constrain the timing and relative magnitudes of changes in the continental weathering and hydrothermal Sr fluxes to the oceans during OAE 2 using a new high-resolution record of seawater 87 Sr/ 86 Sr ratios preserved in a marl-limestone succession from the Iona-1 core collected from the Eagle Ford Formation in Texas. The results show that seawater 87 Sr /86 Sr ratios change synchronously with Os isotope evidence for the onset of massive LIP volcanism 60 kyr before the positive C isotope excursion that traditionally marks the onset of OAE 2. The higher temporal resolution of the seawater Sr isotope record presented in this study warrants a detailed quantitative analysis of the changes in continental weathering and hydrothermal Sr inputs to the oceans during OAE 2. Using an ocean Sr box model, it is found that increasing the continental weathering Sr flux by ∼1.8-times captures the change in seawater 87 Sr/ 86 Sr recorded in the Iona-1 core. The increase in the continental weathering flux is smaller than the threefold increase estimated by studies of seawater Ca isotope changes during OAE 2, suggesting that hydrothermal forcing may have played a larger role in the development of ocean anoxic events than previously considered